Pengaruh Kualitas Produk Dan Kualitas Layanan Terhadap Niat Beli Kembali Melalui Kepuasan Pelanggan Wizzmie di Surabaya - Febri Candra; Lena Ellitan; Yulika Rosita Agrippina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
The food and beverage industry in Indonesia has experienced growth since the Covid-19 pandemic. The development of restaurants selling spicy noodles in Indonesia is increasing. This development is in line with the increasing interest of Indonesians in consuming spicy noodles. Wizzmie is a spicy noodle restaurant that has a wide variety of food and also has good taste quality at affordable prices. This study aims to analyze the effect of product quality and service quality on repurchase intentions with customer satisfaction as mediation on Wizzmie in Surabaya City. This research is a causal type research that analyzes and determines causal relationships. The population in this study are Wizzmie consumers in Surabaya. The sample in this study were 122 respondents who were taken using a questionnaire via Google Form. Respondent data was processed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) technique which was tested using SmartPLS3 software. The results showed that product quality has an effect on repurchase intention, service quality has no effect on repurchase intention, product quality has an effect on customer satisfaction, service quality has an effect on customer satisfaction, customer satisfaction has an effect on repurchase intention. product quality mediated by customer satisfaction has an effect on repurchase intention, service quality mediated by customer satisfaction has an effect on repurchase intention of consumers at Wizzmie in the city of Surabaya.